Effect of aviation fuel temperature on refractive index in droplet size measurement using phase Doppler anemometry. (31st May 2019) - Dafsari, Reza Alidoost; Vashahi, Foad; Chandrahasan, Rakhul; Lee, Jeekeun
Abstract: To accurately measure droplet size using a phase Doppler anemometry (PDA) system, many variables, such as the physical properties of the fuel and optical parameters of the PDA system, should be known, particularly the refractive index of liquid droplets, which is often underestimated. In this study, the effect of a refractive index change on droplet size measurements according to the fuel temperature was experimentally investigated in detail. Light, commercial aviation fuels were used as the working fluids, and a conventional PDA system (DANTEC Co.) was used as the droplet size measuring device. It was confirmed that the change in the refractive index with fuel temperature has a great influence on droplet size measurement. Through extensive experimental investigations, a method for calculating the refractive index according to the fuel temperature change is proposed here.